UPAYA PENINGKATAN KINERJA GURU SEKOLAH KHUSUS SWASTA MELALUI KEPEMIMPINAN DEMOKRATIS, MOTIVASI KERJA, DAN BUDAYA SEKOLAH SE KOTA TANGERANG SELATAN - Susti Wiasih Wiasih; Sri Utaminingsih Utaminingsih; Ersam Mahendrawan Mahendrawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the relationship and influence of democratic leadership, work motivation, and school culture on teacher performance in private special schools in South Tangerang City. This research employed a quantitative approach using an associative research method. The sample consisted of 116 teachers from 21 private special schools in South Tangerang City. Data were collected through validated and reliable questionnaires and analyzed using simple linear regression and multiple linear regression techniques. The results revealed that democratic leadership had a positive and significant effect on teacher performance, with a regression coefficient of 0.993 (t = 17.791; Sig. = 0.001). Work motivation also showed a positive and significant effect on teacher performance, with a regression coefficient of 0.976 (t = 20.669; Sig. = 0.001). In addition, school culture had a positive and significant effect on teacher performance, with a regression coefficient of 0.939 (t = 21.963; Sig. = 0.001). Simultaneously, democratic leadership, work motivation, and school culture had a positive and significant effect on teacher performance, as indicated by an F value of 360.104 (Sig. = 0.001), a correlation coefficient (R) of 0.952, and a coefficient of determination (R²) of 0.906. These findings indicate that 90.6% of the variance in teacher performance can be explained by the combined influence of democratic leadership, work motivation, and school culture. The study concludes that improving teacher performance in private special schools requires a synergistic approach involving democratic leadership practices, strong work motivation, and a supportive school culture.